Validation of the Teacher Questionnaire of Montessori Practice for Early Childhood in the Dutch Context - Jaap de Brouwer; Vivian Morssink-Santing; Symen van der Zee (University of Kansas, 2024)
Montessori education has existed for more than 100 years and counts almost 16,000 schools worldwide (Debs et al., 2022). Still, little is known about the implementation and fidelity of Montessori principles. Measuring implementations holds significant importance as it provides insight into current Montessori practices and because it is assumed that implementation might influence its effectiveness. In the Netherlands, it is especially important to measure fidelity because of the country's history of flexible implementation of Montessori principles. No instruments currently exist that are specifically designed to measure Montessori implementation in the Dutch context. This study aims to validate a translated version of the Teacher Questionnaire for Montessori Practices, developed by Murray et al. (2019), within the Dutch early childhood education context. Additionally, it seeks to investigate the extent to which Montessori principles are implemented in Dutch early childhood schools. Data were collected from 131 early childhood Montessori teachers. Confirmatory factor analysis revealed that the Dutch dataset did not align with the factor structure proposed by Murray et al. (2019). Subsequent exploratory factor analysis led to the identification of a 3-factor solution, encompassing dimensions related to Children's Freedom, Teacher Guidance, and Curriculum, which shows some similarities with Murray et al.'s (2019) factors. Implementation levels in the Netherlands varied, with the highest level of implementation observed in Children's Freedom and the lowest in Curriculum.